(untitled) (Research, Society and Development, 2020)
Every diabetic patient, caregiver / family member should be instructed on the changes present in the feet, as well as clarifying the implications of neuropathy, vascular disease, hygiene care, proper nail cutting and the appropriate footwear to be used. The objective was to evaluate the knowledge of diabetic patients about foot care and to verify adherence after educational intervention during hospitalization, consultation at the outpatient clinic and after hospital discharge. This is a cross-sectional study, carried out with 20 type 2 diabetic patients, attended and guided at a general hospital in Porto Alegre, in two moments: pre-orientation and post-orientation. As a result, 65% of the patients were male and the average age was 60.2 years. There was a statistically significant difference after educational intervention in the following variables: daily examination of the feet (p = 0.008), care for the proper water temperature before washing (p = 0.031), soaking the feet (p = 0.004), moisturizing the feet. feet (p = 0.002), use of socks with seam out or without seams (p = 0.008), cut the nail in the straight shape (p = 0.002), cuticle removal (p = 0.008) and shoes with thick soles and non-slip (p = 0.008). The educational intervention contributed to improve knowledge and allowed the behavioral change reported by the participants about foot care.